Women’s Economic Adaptation Strategies of Poor Heads of Households in the Face of Uncertainty: A Systematic Literature Review - Jumiyanti, Kalzum R.; Ashar, Khusnul; Ekawati, Marlina; Badriyah, Nurul (Journal of Ecohumanism, 2024)
This study examines the economic adaptation strategies of women heads of poor households in developing countries who face a triple burden: poverty, gender discrimination, and lack of support. Using a systematic literature review with the PRISMA approach, data was collected from multiple academic databases, resulting in 29 selected articles from an initial pool of 1,922. The analysis, conducted using the Mixed Methods Appraisal Tool (MMAT), revealed five main adaptation strategies: livelihood diversification, micro business development, food security improvement, non-agricultural activities, and labor migration. Major obstacles include persistent poverty, gender discrimination, and limited access to productive resources. The findings emphasize the need for inclusive and gender-responsive development approaches, suggesting integrated policy interventions such as access to microcredit, skills training, and social protection. This research provides insights into survival strategies of women heads of poor households, contributing to more effective poverty interventions.